Techno-economic assessment of Bilacenge PV grid system in Southwest Sumba - Nurdiana, Eka; Nugroho, Muhammad Very; Fikriyadi, Zakariya Arif; Mardiansah, Fajril; Dianti, Dwie Vannia; Utami, Dannya Maharani Putri; Akhmad, Kholid; Margowadi, Yusuf; Rezavidi, Arya (Journal of Mechatronics, Electrical Power, and Vehicular Technology, 2024)
A solar photovoltaic (PV) grid system with an Energy Management System (EMS) has been installed in Bilacenge, Southwest Sumba. This 400 kWp PV-Grid system is the first system in Indonesia that can control the electricity output to the grid. It comprises two battery blocks that support the system to maximize electricity generation. This study has been conducted to evaluate the installed PV-grid system with EMS compared to diesel generators commonly used in remote areas. The study employs various techno-economic methods, including life cycle cost (LCC), levelized cost of energy (LCoE), and economic feasibility analysis based on several parameters such as net present value (NPV), payback period (PBP), and benefit-cost ratio (BCR). The results show that the system will experience a return on investment after operating for 34 years, accompanied by a benefit-cost ratio value of 0.60, which indicates that the investment of this PV grid system is not economically profitable.